Drought Induced Nepotistic Behaviour in Indian Black Ibis (Pseudibis papillosa) Inhabiting the Arid Zone of Rajasthan, India - Soni, K.C.; Sharma, A.N.; Soni, V.C. (Our Nature, 2009)
Drought induced nepotistic behaviour in the Indian Black ibis (Pseudibis papillosa) inhabiting the arid zone of Rajasthan has been studied. The aim of the present study is to know about any breeding abnormalities induced in the Indian Black ibis by seasonal tragedy like drought. As such the nepotistic behaviour is not found in the Black ibis (Pseudibis papillosa) during normal season. Drought induces a reduced nesting activity and nepotistic behaviour in the Black ibis inhabiting arid zone. The helper birds (Non breeding birds of the own species) become active during drought to assist breeding pairs of Black ibis in various reproductive activities like feeding of breeding female, nestlings, fledglings and defending the nests. The role of helpers in breeding activities of Black ibis during drought also improves their clutch size, hatching success and fledgling success. The significance of the drought induced nepotistic behaviour in Black ibis in view of Hamilton’s theory of kin selection has been discussed. Keywords: Nepotistic behaviour, Black ibis, arid zone, Rajasthan, India doi: 10.3126/on.v6i1.1654 Our Nature (2008)6:47-51